The evolution of pelvic endoprosthetic reconstruction after tumor resection - Ji, Tao; Guo, Wei (Annals of Joint, 2019)
The megaprosthesis is designed to reproduce the form and function of a removed large segment of pelvis. Slow but substantial improvements in the design and surgical implementation of these devices have advanced the capacity to restore patients’ functional abilities. The essential challenges in pelvic reconstruction using endoprostheses include modularity, early stability, biocompatibility, biomechanical compatibility, and durable fixation; these can, ideally, be overcome by osseointegration of the interface and adapting to the physiological condition. The history of pelvic megaprostheses presents unique concepts distinct from those related to other extremities, and improvements that have been made over the past decades will guide the future development of new pelvic endoprostheses. In this review, we try to present the evolution of the pelvic megaprosthesis, focusing on the design style, biomechanical advancement, and the recent development of 3D-printing technology that promise better results and fewer complications. General orthopedic surgeons can also benefit from a general update in this specific area.